2014
DOI: 10.1002/ajh.23604
|View full text |Cite
|
Sign up to set email alerts
|

Parent education and biologic factors influence on cognition in sickle cell anemia

Abstract: Children with sickle cell anemia have a high prevalence of silent cerebral infarcts (SCIs) that are associated with decreased full-scale intelligence quotient (FSIQ). While the educational attainment of parents is a known strong predictor of the cognitive development of children in general, the role of parental education in sickle cell anemia along with other factors that adversely affect cognitive function (anemia, cerebral infarcts) is not known. We tested the hypothesis that both the presence of SCI and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
179
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(196 citation statements)
references
References 41 publications
10
179
0
1
Order By: Relevance
“…29 Beyond the term "silent," which simply indicates the absence of a history of stroke, children who have silent brain lesions on brain MRI scans have been shown to have poorer cognitive function than do children who have normal brain MRI findings. Indeed, in children with SCD, such "silent" lesions have been shown to be associated with a mean decrease in full-scale IQ of 5 points, 30 poor academic performance, 31 and a higher risk of overt strokes. Values are mean (6 SD), unless otherwise indicated.…”
Section: Discussionmentioning
confidence: 99%
“…29 Beyond the term "silent," which simply indicates the absence of a history of stroke, children who have silent brain lesions on brain MRI scans have been shown to have poorer cognitive function than do children who have normal brain MRI findings. Indeed, in children with SCD, such "silent" lesions have been shown to be associated with a mean decrease in full-scale IQ of 5 points, 30 poor academic performance, 31 and a higher risk of overt strokes. Values are mean (6 SD), unless otherwise indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Among children with sickle cell anemia, results from the Silent Infarct Transfusion Trial predict an average decrease of a child's intelligence quotient (IQ) by 1 point per year, regardless of the presence of a silent cerebral infarct. 16 Given the relationship between IQ and career attainment, these outcomes are equally important to those with sickle cell disease.…”
Section: Reconsideration Of Age As a Contraindication For Curative Thmentioning
confidence: 99%
“…haematocrit <20%) have shown poorer performance on both verbal and performance aspects of IQ [119], and have accounted for a significant proportion of variance in FSIQ [64,138] and executive functions [64].Low nocturnal peripheral oxygen saturation was associated with reduced performance on the Tower of London test, which measures strategic planning and rule learning [139]. In the baseline data from the Silent Infarct Trial, a 1% reduction in daytime oxygen saturation was associated with a reduction in 0.75 full scale IQ points [122].…”
Section: Non-imaging Biomarkers Of Functionmentioning
confidence: 99%
“…Large cohort studies have found socioeconomic status and parent education as major predictors of cognitive function, rather than SCI [122,141].…”
Section: Sickle Cell Disease -Pain and Common Chronic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation